2018
DOI: 10.1002/cm.21472
|View full text |Cite
|
Sign up to set email alerts
|

PKC epsilon signaling effect on actin assembly is diminished in cardiomyocytes when challenged to additional work in a stiff microenvironment

Abstract: The stiffness of the microenvironment surrounding a cell can result in cytoskeletal remodeling, leading to altered cell function and tissue macrostructure. In this study, we tuned the stiffness of the underlying substratum on which neonatal rat cardiomyocytes were grown in culture to mimic normal (10 kPa), pathological stiffness of fibrotic myocardium (100 kPa), and a nonphysiological extreme (glass). Cardiomyocytes were then challenged by beta adrenergic stimulation through isoproterenol treatment to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
(76 reference statements)
0
7
0
1
Order By: Relevance
“…7) suggests that the actin binding face (site 1) and the β-tentacle (site 2) cooperate to regulate CapZ docking to the actin filament. This model is based on the new results, other investigations (Kim et al, 2007; Kuhn and Pollard, 2007; Smith et al, 2006), and our prior work (Hartman et al, 2009; Li and Russell, 2013; Lin et al, 2013, 2015, 2016; Li et al, 2014, 2016; Mkrtschjan et al, 2018). We propose the tight binding is loosened in growth states of hypertrophy triggered by stimuli such as mechanical flexing, loading, stiffer substrate, angiotensin II, and phenylephrine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7) suggests that the actin binding face (site 1) and the β-tentacle (site 2) cooperate to regulate CapZ docking to the actin filament. This model is based on the new results, other investigations (Kim et al, 2007; Kuhn and Pollard, 2007; Smith et al, 2006), and our prior work (Hartman et al, 2009; Li and Russell, 2013; Lin et al, 2013, 2015, 2016; Li et al, 2014, 2016; Mkrtschjan et al, 2018). We propose the tight binding is loosened in growth states of hypertrophy triggered by stimuli such as mechanical flexing, loading, stiffer substrate, angiotensin II, and phenylephrine.…”
Section: Discussionmentioning
confidence: 99%
“…Substrate stiffness varies in health and disease (Bhana et al, 2010; Fomovsky and Holmes, 2010), and stiffness has been shown to regulate actin assembly and cell size (Li et al, 2016; Mkrtschjan et al, 2018). FRAP data (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac myofilament phosphorylation is mediated by a number of different kinases. Work by us (7)(8)(9)(10)14) and others (18)(19)(20)(21) have found that CapZ influences myofilament regulation by protein kinase C (PKC) and is a substrate for this family of kinases. To determine how exercise alters myofilament-associated PKC and if a decrease in cardiac CapZ levels alters exercisedependent changes in sarcomeric PKC we probed isolated cardiac myofilaments for PKC- (calciumdependent isoform) and PKC- (calcium independent isoform).…”
Section: Reduced Capz Alters Myofilament Functional Response To Exercmentioning
confidence: 99%
“…Los virus adeno-asociados que contienen los ADN codificantes de CapZβ1-GFP y la forma truncada de CapZ que carece de los 12 últimos amino ácidos en la C-terminal (CapZβ1ΔC-GFP) fueron preparados como se ha descrito previamente (Lin et al 2013) Ensayos de Fluorescence Recovery After Photobleaching (FRAP) fueron realizados en cardiomiocitos infectados con CapZβ1-GFP o CapZβ1ΔC-GFP, mientras que los ensayos de Förster Resonance Energy Transfer (FRET) fueron hechos mediante la incorporación de un anticuerpo específico para PIP2 (Abcam #2335) como se ha descrito previamente (Mkrtschjan et al 2018). Neomicina (500 μM, 30 min) fue utilizada para inhibir la disponibilidad intracelular de PIP2.…”
Section: Metodologíaunclassified